2021
DOI: 10.1016/j.jad.2020.10.061
|View full text |Cite|
|
Sign up to set email alerts
|

Self-reported changes in anxiety, depression and suicidality during the COVID-19 lockdown in Greece

Abstract: Highlights During the lockdown: Clinical depression was present in 9.31% Severe distress was present in 8.5% Increased anxious and depressive emotions were present in more than 40%. 23.31% experienced a relapse of depression 8.96% of cases without previous history, who manifested their first depressive episode. Beliefs in conspiracy theories were widely prevalent, with, on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
135
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 34 publications
13
135
4
2
Order By: Relevance
“…The first COVID-19 case in Greece was announced on 26th February 2020 and the first wave of the outbreak was mostly benign following the implementation of a successful lockdown during the initial phase of the crisis; restrictions were imposed early, and lockdown measures were largely adhered to by the public. However, studies conducted during this period in the general population showed high levels of depression and anxiety symptoms which were similar or higher compared to past assessments especially when compared to the period preceding the 2009 economic crisis, due to the already heightened prevalence rates amid the recession in the country [ 16 , 17 ]. A strong emotional impact of the epidemic was observed more often in women and in those with severe financial difficulties, and depressive symptoms were higher in the younger, in students and in those isolated due to symptoms or overexposed to media for COVID-19-related news [ 18 ].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The first COVID-19 case in Greece was announced on 26th February 2020 and the first wave of the outbreak was mostly benign following the implementation of a successful lockdown during the initial phase of the crisis; restrictions were imposed early, and lockdown measures were largely adhered to by the public. However, studies conducted during this period in the general population showed high levels of depression and anxiety symptoms which were similar or higher compared to past assessments especially when compared to the period preceding the 2009 economic crisis, due to the already heightened prevalence rates amid the recession in the country [ 16 , 17 ]. A strong emotional impact of the epidemic was observed more often in women and in those with severe financial difficulties, and depressive symptoms were higher in the younger, in students and in those isolated due to symptoms or overexposed to media for COVID-19-related news [ 18 ].…”
Section: Introductionmentioning
confidence: 81%
“…In our study, the levels of depression and anxiety in HCWs were higher or similar to those reported in the general Greek population around the same period of time, although these may be difficult to compare due to the different methodologies used across studies. Clinical depression was present in 9.3% and increased anxiety in more than 45% of the sample in a study by Fountoulakis et al [ 17 ], whereas suicidal thoughts increased in 10.4% and decreased in 4.4%. In another study, a significant proportion reported moderate to severe depressive symptoms (22.8%), moderate to severe anxiety symptoms (77.4%) or COVID-19-related fear (35.7%), with women scoring altogether significantly higher than men [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the health impact of public life restrictions related to COVID-19 has mostly been examined in individual countries. For instance, reports from China ( 6 , 7 ), Italy ( 8 ), and Greece ( 9 ) suggest considerable increases in anxiety and depression. As confinement measures affect an estimated minimum of 4 billion people worldwide ( 10 ), exploring changes in mental well-being on a multinational scale is an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of confirmed cases and deaths, resulting to a fatality rate of 1.9% in November, further increased fear and uncertainty. At a social level, polarization between those who were attentive and those who were careless started to grow, as continuous reminders of the magnitude of the health crisis were projected across the media span (Fountoulakis et al, 2020 ). In addition, worry about the financial aftermath was significant among professionals in the private sector, whereas the public sector had minimal or no pay cuts (Economides et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%